The Threshold of a Stochastic SIRS Model with Vertical Transmission and Saturated Incidence - Chunjuan Zhu; Guangzhao Zeng; Yufeng Sun (Discrete Dynamics in Nature and Society)
The threshold of a stochastic SIRS model with vertical transmission and saturated incidence is investigated. If the noise is small, it is shown that the threshold of the stochastic system determines the extinction and persistence of the epidemic. In addition, we find that if the noise is large, the epidemic still prevails. Finally, numerical simulations are given to illustrate the results.